Ethics as a Potential Demarcation Line Between Lobbying and Trading in Influence - Sporea, Danijel (Political Life, 2026)
Abstract: Lobbying has become an important component of the political system in contemporary democratic states. Its increasing involvement in decision-making processes requires democratic governments to incorporate it into legal frameworks and ensure its implementation in accordance with the rule of law. Lobbying practices conducted without adequate regulation and transparency may lead to forms of corrupt conduct and create the perception of trading in influence. For this reason, it is essential that ethics be not only acknowledged but effectively applied in the process of regulating this activity. By establishing clear ethical boundaries, lobbying can ensure that individuals engaged in lobbying activities are properly distanced from illegitimate and harmful practices. In addition to offering a theoretical examination of the nature of lobbying and ethics, the author seeks, through a critical analysis of key documents and laws governing these activities, to assess the extent to which codes of ethics prevent trading in influence, proceeding from the premise that they establish normative frameworks within which lobbying must be conducted. Aligning lobbying practices with ethical standards may lay the foundation for a more professional approach to lobbying, thereby reshaping its negative public image, particularly its perception as a tool for advancing private interests closely associated with trading in influence and corruption.